Development of STEM-Based Evaluation Tools for Economic Learning in SMA East Java in the Education Era 4.0 - Handayani, Sri; Mintarti, Sri Umi; Rachmawati, Dian; Wahyonono, Hari (KnE Social Sciences, 2021)
Learning in the education era 4.0 requires strengthening skills in reaching the golden generation of 2045. According to the STEM Team (2019), there are three core skills of the 21st century, which is the era of education 4.0. These are: 1) character quality consisting of religiosity, nationalism, independence, mutual cooperation and integrity; 2) basic literacy consisting of language, numeracy, scientific, digital, financial and cultural literacy and citizenship; and 3) competencies consisting of critical thinking, creativity, communication and collaboration. To achieve these skills, an appropriate evaluation tool is needed which is tailored to these characteristics. One evaluation model that can be developed is STEM-based evaluation. Rahmatina (2020) states that STEM is learning that integrates science, technology, engineering and mathematics. This study aimed to develop a STEM-based evaluation tool that fits the characteristics of the education era 4.0. Development research methods were used. Borg & Gall (1983: 775) described the stages carried out, namely research and information collecting, planning, developing preliminary forms of the product, preliminary field testing, main product revision, main field testing, operational product revision, and dissemination and implementation. Keywords: STEM, Evaluation Tools, Economic Learning